Dielectric and electromagnetic wave absorption properties of reduced graphene oxide/barium aluminosilicate glass–ceramic composites. Issue 6 (1st May 2016) - Li, Mian; Yin, Xiaowei; Chen, Lingqi; Han, Meikang; Cheng, Laifei; Zhang, Litong
Abstract: BaAl2 Si2 O8 (BAS) glass–ceramic powders were prepared by sol–gel method. Graphene oxide (GO)/BAS mixture powders were prepared by a simple mixing process of GO and BAS. Dense and uniform reduced graphene oxide (RGO)/BAS composites were fabricated by the hot-pressing of GO/BAS, which was accompanied by the in-situ thermal reduction of GO. Microstructure, phase composition, dielectric and electromagnetic wave (EM) absorption properties of RGO/BAS were investigated. The results reveal that RGO can promote the hexacelsian-to-celsian phase transformation of BAS. In the frequency range from 8 GHz to 12 GHz, the complex permittivity of RGO/BAS increases with increasing RGO content. The composite with 1.5 wt% of RGO shows good EM absorbing ability. When the sample thickness is 2.1 mm, the minimum reflection coefficient (RC) reaches −33 dB, and the effective absorption bandwidth is more than 3.1 GHz.